Implementasi dan Analisis Wazuh Sebagai Intrusion Detection System (IDS) dan Platform Monitoring - Gede Parama Antara; Ika Dyah Agustia Rachmawati (Politeknik Negeri FakFak, 2024)
Attacks on web applications (web application attacks) can compromise data security in hospitals which are exploited by attackers by using weaknesses in the web application code. However, there are still many developers who are less alert to attacks on web applications. To improve the security side of the web server so that it detects suspicious attacks in website network traffic, namely by using wazuh as an Intrusion Detection System (IDS) and monitoring platform. The evaluation results show that the implementation of wazuh as an Intrusion Detection System (IDS) and monitoring platform can detect attacks by closing security gaps so that attackers cannot attack in the same way.